Failure and success in mergers and acquisitions - Renneboog, Luc; Vansteenkiste, Cara (Journal of Corporate Finance, 2019)
This paper provides an overview of the academic literature on the market for corporate control, and focuses specifically on firms' performance around and after a takeover. Despite the aggregate M&A market amounting to several trillions USD on an annual basis, acquiring firms often underperform relative to non-acquiring firms, especially in public takeovers. Although hundreds of academic studies have investigated the deal- and firm-level factors associated with M&A announcement returns, short-run returns are often not sustained in the long run. Moreover, the wide variety of performance measures and heterogeneity in sample sizes complicates the drawing of accurate and unambiguous conclusions. In this light, our survey compiles the recent literature and aims to identify the areas of research for which short-run returns predict (or fail to predict) long-run performance. We find that post-takeover deal performance is affected by key determinants including serial acquisitions, CEO overconfidence, acquirer-target relatedness and complementarity, and shareholder intervention in the form of voting or activism.